The Statutory Safe Harbor for Forward-Looking Statements After Two and a Half Years: Has It Changed the Law? Has it Achieved What Congress Intended? - Richard A. Rosen (Washington University Law Quarterly, 1998)
This Article examines the safe harbor for projections and forward-looking statements created by the Private Securities Litigation Reform Act of 1995.
Keywords: Securities fraud; Business forecasting; Disclosure (Securities law); Financial statements; Private Securities Litigation Reform Act of 1995